2023
DOI: 10.5194/egusphere-egu23-958
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Response of the ENSO-driven CO2 flux variability in the equatorial Pacific under high-warming scenario

Abstract: <div class="page" title="Page 1"> <div class="section"> <div class="layoutArea"> <div class="column"> <p>The El Niño–Southern Oscillation (ENSO) widely modulates the global carbon cycle. More specifically, it alters the net uptake of carbon in the tropical ocean. Over the tropical Pacific, less carbon is released during El Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…For example, Vaittinada Ayar et al. (2022) shows that IPSL‐CM6A‐LR doesn't have a strong alkalinity bias, however, we find that its pCO 2, nonT : pCO 2, T variance ratio is weaker than the ratio in MRI‐ESM2‐0 (Figure 7b), which is a model they show with a strong alkalinity bias.…”
Section: Discussioncontrasting
confidence: 47%
See 4 more Smart Citations
“…For example, Vaittinada Ayar et al. (2022) shows that IPSL‐CM6A‐LR doesn't have a strong alkalinity bias, however, we find that its pCO 2, nonT : pCO 2, T variance ratio is weaker than the ratio in MRI‐ESM2‐0 (Figure 7b), which is a model they show with a strong alkalinity bias.…”
Section: Discussioncontrasting
confidence: 47%
“…Previous studies of historical simulations from the earlier CMIP5 found that FCO 2 IAV were also underestimated in models (Dong et al., 2016, 2017). Results from another CMIP6 study also find that most models simulate weak FCO 2 anomalies while overestimating SST IAV (Vaittinada Ayar et al., 2022).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations